2008
DOI: 10.2147/tcrm.s3437
|View full text |Cite
|
Sign up to set email alerts
|

Management of postoperative nausea and vomiting: focus on palonosetron

Abstract: Postoperative nausea and vomiting (PONV) remains a signifi cant problem in modern anesthetic practice, with an incidence in high-risk groups of up to 80%. In addition to being unpleasant and distressing for the patient, PONV has the potential to adversely affect patient and surgical outcomes. Advances in PONV prophylaxis over recent years include using non-pharmacological means to reduce baseline risk, a change to less emetogenic anesthetic techniques and the combination of multiple antiemetic drugs. The 5-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 138 publications
0
6
0
Order By: Relevance
“…Although 0.075 mg of palonosetron is an approved dose for the control of PONV for 24 hours after surgery, [26] the efficacy of single injection would be maintained for much longer time after treatment, due to its long half-life of 40 hours [27] . Especially, palonosetron is known to work better in delayed nausea and vomiting [6] . Additional studies would be needed for validation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although 0.075 mg of palonosetron is an approved dose for the control of PONV for 24 hours after surgery, [26] the efficacy of single injection would be maintained for much longer time after treatment, due to its long half-life of 40 hours [27] . Especially, palonosetron is known to work better in delayed nausea and vomiting [6] . Additional studies would be needed for validation.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Especially, palonosetron is known to work better in delayed nausea and vomiting. [6] Additional studies would be needed for validation. Fourthly, we checked some side effects related to the use of midazolam including drowsiness, headache, and dizziness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative emesis not only predisposes patients to wound dehiscence and psychological distress (3), but frequently delays their discharge from the hospital after planned ambulatory surgery (4). The ondansetron and palonosetron as first and second generation of 5-hydroxytryptamine-3 (5-HT3) receptor antagonists are commonly used for the prevention of PONV in moderate to high-risk patients because of better efficacy and favorable side effects as compared to other antiemetics (5,6). Compared with ondansetron, palonosetron has greater affinity for 5-HT3 receptors (7), although a recent meta-analysis has shown that palonosetron was not more efficacious than ondansetron in the prevention of early PONV after laparoscopic surgery (8).…”
Section: Introductionmentioning
confidence: 99%